Influences of configuration and coating on the vibration characteristics of spindles - Hechun Yu; Bo Zhang; Jin Wang; Hepeng Cheng; Guoqing Zhang; Wenbo Wang; Renzong Wang (The Journal of Engineering, 2022)
Abstract Strong vibration is the main factor leading to the spinning spindle failure, which is closely related to the spindle end configuration and surface coating. In this study, the effects of the spindle end configuration and surface coating on the vibration characteristics of spinning spindles are studied, the vibration tests were conducted on a multifunctional spindle test bench by using three different types of spindles without coating and the YD4203C pointed spindle with surface self‐lubricating coating under various high‐speed no‐load conditions. The results showed that the vibration phenomenon of the YD4203C pointed‐head spindle was slighter than that of YD6111FA frustum spindle and YD6100E flat‐headed spindle, this was believed to be because the increase in the end surface area could speed up the heat transfer, and the decrease in the bottom area of the spindle end could reduce the impact of the high‐speed oil and gas vortex on the vibration. In addition, the vibration characteristics of the coated YD4203C pointed spindles are significantly improved compared with the uncoated spindles. This study provides the experimental basis for the design and manufacture of spindles with low vibration.